Pengaruh Konflik Peran, Ketidakjelasan Peran, dan Kelebihan Peran terhadap Kepuasan Kerja dan Kinerja Auditor (Penelitian pada Kantor Akuntan Publik yang Bermitra Dengan Kantor Akuntan Publik Big Four di Wilayah DKI Jakarta) - Lidya Agustina (Jurnal Akuntansi)
The purpose of this research is to analyze and examine the hypothesis The Effect of Role Conflict, Role Ambiguity, and Role Overload on Job Satisfaction & Performance of junior auditor who work at Public Accountant Firm that has cooperation with big four Public Accountant Firms in DKI Jakarta simultaneously or partiality. This research performed at 93 junior auditors who work in between one until three years at public accountant firm that has cooperation with big four public accounting firms in DKI Jakarta at 2008.